Implementation of COBIT 2019 for Designing Hospital Performance Improvement Recommendations - Radja, Carrisa Adnyana Putri; Budiraharjo, Raden; Chazar, Chalifa (Sistemasi: Jurnal Sistem Informasi, 2025)
Service delivery at Kiwari Regional Public Hospital (RSUD Kiwari) in Bandung continues to face various challenges in meeting established standards. These challenges primarily stem from inefficiencies in business processes, particularly in patient registration, medical consultations, inpatient services, and patient transfers. These issues were previously identified through bottleneck analysis using a process mining approach. The identified bottlenecks indicate delays in several stages of the hospital service process. This study aims to provide improvement recommendations to enhance the hospital's business process capabilities based on the bottleneck analysis results obtained from process mining. The research adopts the COBIT 2019 framework to assess and improve business process capabilities, with a focus on the DSS06 (Deliver, Service, and Support) domain, deemed most relevant to the hospital’s current challenges. COBIT 2019 was selected for its systematic approach to measuring and enhancing IT process capabilities. The findings indicate that the current business process capability level at RSUD Kiwari Bandung is at Level 2, while the target level is Level 3. To achieve this goal, the study proposes a set of improvement recommendations that can serve as an evaluation tool and a guide to improving IT governance and service efficiency at RSUD Kiwari Bandung.